PREDIKSI KELAYAKAN PEMBERIAN FASILITAS KARTU KREDIT KEPADA NASABAH DENGAN METODE KLASIFIKASI DATA MINING (STUDI KASUS : BANK XYZ) - Ferdinand Stevanus Alvian; Selawati Carbini; Komarudin Komarudin (STMIK Mardira Indonesia, Bandung, 2020)
As one of the largest banks in Indonesia and in the midst of competition between existing banking institutions, Bank XYZ participates in providing credit to customers in the form of credit cards. The provision of credit card facilities for customers at Bank XYZ must go through a customer screening process and check data in depth so that banks can avoid non-current customer credit. One way that banks can use is by using the data mining method. In this study, two models were compared in the classification method, namely Discriminant Analysis and Naïve Bayes. Keywords: Data Mining, CRISP-DM, Discriminant Analysis.DOI : http://doi.org/10.5281/zenodo.4320278